ELECTROSPUN NANOFIBER-COATED MEMBRANE: A REVIEW (Jurnal Teknologi (Sciences & Engineering), 2016)
The nanofibre development offers various useful applications in many ways including energy and environmental application. Polymeric nanofibre fabricated by electrospinning has been seen as innovative membrane materials for water remediation owing to the high surface area, interconnected porous structure, and light weight. This paper reviews the exciting functionality of nanofibre involving the development of smart heterogeneous approaches in membrane material. These heterogeneous materials allow the water molecules to spontaneously penetrate from one side to another, while blocking penetration in reverse direction due to hydrophilic-hydrophobic differences. Composite membrane containing different features arrangements of nanofibres have been utilised for their ability for water applications especially in membrane distillation.